2019
DOI: 10.1177/1010539519879322
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Clusters of Diabetes and Physical Inactivity: Do Neighborhood Characteristics in High and Low Clusters Differ?

Abstract: This study aims to find spatial clusters of diabetes and physical inactivity among a sample population in Kerala, India, and evaluate built environment characteristics within the high and low spatial clusters. Spatial clusters with a higher and lower likelihood of diabetes and physical inactivity were identified using spatial scan statistic at various radii. Built environment characteristics were captured at panchayat level and 1600 m buffer around participant location using Geographical Information Systems. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 28 publications
(34 reference statements)
2
18
0
Order By: Relevance
“…Although adjusting for socioeconomic and demographic factors did not modify the distribution or the characteristics of the clusters, we did highlight an older population and a higher proportion of non-workers in low raw MVPA clusters, and a lower neighborhood household income in low MVPA clusters after adjustment for socioeconomic and demographic factors. Huang et al [20], Tamura et al [18], and Valson et al [22] also found inconsistent findings related to socioeconomic determinants and spatial clusters of physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although adjusting for socioeconomic and demographic factors did not modify the distribution or the characteristics of the clusters, we did highlight an older population and a higher proportion of non-workers in low raw MVPA clusters, and a lower neighborhood household income in low MVPA clusters after adjustment for socioeconomic and demographic factors. Huang et al [20], Tamura et al [18], and Valson et al [22] also found inconsistent findings related to socioeconomic determinants and spatial clusters of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have explored the association of the built environment with physical activity from a geographic perspective have found mixed evidence [18, 19, 21]. However, there is an overall agreement that environments that favor walkability, such as higher population density (urbanicity) and street connectivity, are associated with higher physical activity levels [17, 18, 20, 22]. In contrast, we did not find a positive association between a higher land use area coverage with the spatial clusters of high physical activity [17, 18, 22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations